The Effect of Brief Anxiety Interventions on Reported Anxiety and Math Test Performance - Colleen M. Ganley; Rachel A. Conlon; Amanda L. McGraw; Connie Barroso; Elyssa A. Geer (Journal of Numerical Cognition, 2021)
Research suggests that math and test anxiety have detrimental impacts on performance in math. To prevent these effects, a number of interventions have been developed, but these interventions have not been extensively tested. In the current study, we examine whether four brief anxiety interventions reduce state anxiety and/or increase math performance. We also examine whether any of the interventions weaken the relation between math or test anxiety and math performance. Participants were 300 college students varying in math and test anxiety levels. Participants were randomly assigned to one of four single-session interventions, which each took 5 minutes or less (reappraisal as challenge, reappraisal as excitement, expressive writing, and look ahead), or a no intervention control group. Results generally show that none of the interventions had an effect on reports of state anxiety or performance on a difficult math assessment, with the exception that students in the expressive writing condition reported higher levels of state anxiety. None of the interventions served to attenuate the relation between math or test anxiety and math performance. These findings were not consistent with results of previous work, and suggest that interventions may need to be more extensive in order to have an effect on state anxiety and math performance.